(untitled) (New York, 2010)
Students can access selections as well as practice and supportfor fluency, vocabulary, and comprehension.? The systematic, explicit instructional plan for SRA Imagine It! helps you build students' abilities through a logical profession of skills. Core concepts and skills are reinforced at every level to scaffold the foundation for your students' most critical reading and comprehension skills. Thought-provoking themes and genres introduce your students to new worlds, new ideas, and new ways of thinking.The Literature, novels, essays, poems, songs and articles found in SRA Imagine It! are a diverse collection of fiction and nonfiction reading selections that inspire and challenge students to become independent, self-directed readers. Find them in a variety of program materials:Friendship animals and their habitats money
Keywords: Giáo dục, tiểu học,Education, elementary; Hoa Kỳ,United states